Virtual Reality Technology in the Treatment of Autism Spectrum Disorder - Bouhidel, Chouaib; Bahtane, Abdelkader (Journal of Human Sciences, 2021)
Autism Spectrum Disorder (ASD) is considered one of the most important disorders of interest to psychologists and child psychiatrists in various countries around the world. Despite this, no curative and definitive treatment has been found in this direction, in addition to its wide spread, which may have doubled the fears of families for the future of their children. Although the research has not stopped, but has escalated. In this context, our research is interested in the psychological literature, through ten studies, on the measurement of virtual reality and its use as a therapeutic technique for ASD. The results showed that this technology has a promising future due to the interaction of children with it on the one hand, and on the other hand, its positive impact on the development of certain aspects of the personality of a child with ASD. In particular the development of social and communicational interactional capacities.